Autophagy induction during stem cell activation plays a key role in salivary gland self-renewal. Issue 2 (1st February 2022) - Orhon, Idil; Rocchi, Cecilia; Villarejo-Zori, Beatriz; Serrano Martinez, Paola; Baanstra, Mirjam; Brouwer, Uilke; Boya, Patricia; Coppes, Rob; Reggiori, Fulvio
ABSTRACT: Relatively quiescent tissues like salivary glands (SGs) respond to stimuli such as injury to expand, replace and regenerate. Resident stem/progenitor cells are key in this process because, upon activation, they possess the ability to self-renew. Macroautophagy/autophagy contributes to and regulates differentiation in adult tissues, but an important question is whether this pathway promotes stem cell self-renewal in tissues. We took advantage of a 3D organoid system that allows assessing the self-renewal of mouse SGs stem cells (SGSCs). We found that autophagy in dormant SGSCs has slower flux than self-renewing SGSCs. Importantly, autophagy enhancement upon SGSCs activation is a self-renewal feature in 3D organoid cultures and SGs regenerating in vivo . Accordingly, autophagy ablation in SGSCs inhibits self-renewal whereas pharmacological stimulation promotes self-renewal of mouse and human SGSCs. Thus, autophagy is a key pathway for self-renewal activation in low proliferative adult tissues, and its pharmacological manipulation has the potential to promote tissue regeneration.